Panentheism and Progressive Christianity. Issue 2 (1st April 2022) - Webb, Val
Abstract : Progressive Christianity is an eclectic, often lay-led momentum spreading across the Christian landscape, challenging various aspects of Christian tradition in light of contemporary knowledge, culture and contexts. The momentum is not new, as similar challenges have been raised against 'orthodox' Christianity since its beginnings. Progressive concerns include intellectual integrity, interfaith dialogue, ecotheology, creative worship, spiritual vitality and the inclusion of disenfranchised people. Panentheism's view of God and the cosmos in relationship, affecting and affected by each other, rather than supernatural theism's 'wholly other' God independent of the world, provides new language and conceptualisation which help to address the challenges that progressives raise.